2006
DOI: 10.1542/peds.2005-0267
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Counseling for Mothers of Very Low Birth Weight Infants: Effect on Maternal Anxiety and Infant Intake of Human Milk

Abstract: OBJECTIVE. Although it is well documented that breastfeeding promotes health and development of very low birth weight (VLBW) infants, lactation initiation among mothers of VLBW infants is low. Mothers are anxious about the health of their children, and medical staff may be reluctant to promote breastfeeding out of concern for increasing that anxiety. Therefore, the purpose of this study was to examine whether mothers of VLBW infants who initially planned to formula feed were different in terms of their level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 31 publications
2
120
1
10
Order By: Relevance
“…31 Providing lactation education and lactation support is effective at achieving high lactation initiation and duration of milk expression among mothers of VLBW infants. 19,32 We acknowledge that there are limitations of this study. First, the data were collected primarily for another purpose and for this present analysis of the association between high intake of HM and risk of NEC, the study power was relatively modest.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…31 Providing lactation education and lactation support is effective at achieving high lactation initiation and duration of milk expression among mothers of VLBW infants. 19,32 We acknowledge that there are limitations of this study. First, the data were collected primarily for another purpose and for this present analysis of the association between high intake of HM and risk of NEC, the study power was relatively modest.…”
Section: Discussionmentioning
confidence: 96%
“…Study participants were delivered between May 2001 and August 2003, with birth weight between 700 and 1500 g. Their mothers participated in a study comparing anxiety levels before and after lactation counseling. 19 A prospective sample of 200 mother-infant pairs was targeted to provide a basis for detecting a pre-intervention/post-intervention difference of 0.4 standard deviation at 80% power in the State Trait Anxiety Scores, assuming a standard deviation of 10.6. Exclusion criteria for that study were illicit drug use during pregnancy, human immunodeficiency virus infection, age less than 18 years, and nonEnglish speaking.…”
Section: Sample and Settingmentioning
confidence: 99%
“…A Cochrane review of 34 trials (29 385 dyads) showed a lower risk 23 In a study of lactation consultant counseling in mothers of very low birth weight infants, after counseling was performed 85% of 81 mothers who initially planned to formula feed their infants initiated breastfeeding, and 100% of mothers who had initially intended to breastfeed were able to do so. 24 The investigators also demonstrated through psychological testing that this counseling did not increase maternal anxiety levels in either group. This runs counter to a belief that breastfeeding creates a burden on already-stressed mothers of NICU-admitted infants.…”
Section: Nicu Admission and Breastfeeding Prams 2000 To 2003mentioning
confidence: 95%
“…[2][3][4] Insufficient production in the first 6 weeks postpartum is the most common reason for discontinuing lactation, 2.8 times more frequent in mothers of preterm than those of term infants. [5][6][7] Also, average milk output in mothers of preterm infants has been shown to falter after 2 to 3 weeks, decline over the next 3 weeks and consistently remain below that of mothers of term infants. 6 Mothers of preterm infants are pump dependent for months before establishing non-pump-dependent breastfeeding, making the sustained, upward trajectory of milk production over months the critical factor.…”
Section: Introductionmentioning
confidence: 99%
“…For example, race and socioeconomic factors influence initiation rates for term infant mothers, but not for mothers who deliver prematurely and learn the protective benefits of their milk. 7 Modifiable variables are pumping initiation (time between birth and first expression), frequency and duration, and the longest interval between two pumping sessions (potential sleeping time). However, few studies have evaluated the use of manual techniques to increase milk yield and/or milk quality.…”
Section: Introductionmentioning
confidence: 99%